القياس اللغوي: تطوّر معناه في الدراسة العربية - Fazlur Rachman (Al-Ma‘rifah, 2017)
Qiyas (analogy) is considered as one of the important methods in which Arabic is developed in the early centuries. It serves as the base or source of the new words or structures which are not found earlier in Arabs daily speeches. The scholars utilized it as a tool to separate the authentic ones of Arab words from many of those had been witnessed only by few. Qiyas across the ages has evolved in stages. The practice of qiyas by early scholars does not mean the same by the late ones. This research attempts to reveal the nature of qiyas; its definitions, stages of its development and its importance in the development of the Arabic language. This research is descriptive analytical research which the researcher tries to describe the definition of qiyas among Arabic scholars across the ages and the evolution of its meaning and the way scholars use it in their linguistic explanations in developing of linguistic subjects.